2022
DOI: 10.3390/min12030344
|View full text |Cite
|
Sign up to set email alerts
|

Apatite U-Pb Dating and Composition Constraints for Magmatic–Hydrothermal Evolution in the Giant Renli Nb-Ta Deposit, South China

Abstract: Apatite is a nearly ubiquitous accessory phase in igneous rocks that crystallizes during the entire magma evolution process and has great implications for geochronology and petrogenesis. Previous studies suggested that Nb-Ta mineralization in the giant Renli deposit was genetically related to Late Jurassic two-mica monzogranite or Early Cretaceous muscovite monzogranite. Moreover, the magmatic–hydrothermal evolution of these two stages is poorly understood. In our study, we confirm that the muscovite monzogran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…The Shihuiyao granites display enrichment in Rb, Li and K, and depletion in Ba, Sr, P, Ti, Mg and Ca, suggesting a continental crust origin [46]. They have high SiO 2 contents (73.66-77.08 wt%) and Mg # values (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), consistent with crust-derived melts [47]. Low Ti/Zr (1.14-2.77) and Ti/Y (5.95-21.52) ratios are also similar to the crustal values (<20 and <200, respectively) [48].…”
Section: Magma Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…The Shihuiyao granites display enrichment in Rb, Li and K, and depletion in Ba, Sr, P, Ti, Mg and Ca, suggesting a continental crust origin [46]. They have high SiO 2 contents (73.66-77.08 wt%) and Mg # values (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), consistent with crust-derived melts [47]. Low Ti/Zr (1.14-2.77) and Ti/Y (5.95-21.52) ratios are also similar to the crustal values (<20 and <200, respectively) [48].…”
Section: Magma Sourcementioning
confidence: 99%
“…In recent years, vigorous explorations have been carried out with the aim of discovering new rare-element mineral deposits in China. Previous research in South China has proposed a linkage between highly evolved granites and rare-element mineralization (e.g., Renli Nb-Ta, Shizhuyuan W-Sn and Jiepailing Sn-Be-F deposits in Hunan Province [1][2][3][4]; Yichun Ta-Nb and Xihuashan W-Be-REE deposits in Jiangxi Province [5,6]). Highly evolved raremetal-bearing granites are small bodies, but they are major suppliers of several "critical" rare metals (e.g., Li, Be, Rb, W, Sn, Nb, Ta).…”
Section: Introductionmentioning
confidence: 99%
“…A good number of studies have concluded that apatite is a key mineral in magmatichydrothermal systems to record their crystallization history and to reflect the melt composition and oxidation conditions [2,4,[6][7][8]10,11,15,17,21,124,132,153]. Moreover, compositional variations of apatite may help to determine the economic potential and fertility index in different ore deposit environments, including granitoids (e.g., [7,10,134]); pegmatites, (e.g., [10,16,49,154,155]); carbonatites (e.g., [10,23]); skarns (e.g., [11]); Sn, W and Mo deposits (e.g., [6,11]); Cu-porphyry [156,157]; and Au-epithermal deposits [26] among others.…”
Section: Apatite As Archive Of Processes In Granitic and Pegmatitic S...mentioning
confidence: 99%